2022
DOI: 10.1080/15384047.2022.2054244
|View full text |Cite
|
Sign up to set email alerts
|

NEDD4L inhibits glycolysis and proliferation of cancer cells in oral squamous cell carcinoma by inducing ENO1 ubiquitination and degradation

Abstract: Glycolysis contributes to cell metabolism and facilitates cell proliferation of oral squamous cell carcinoma (OSCC), the most common type of oral cancer. Understanding the regulatory mechanisms involved in the glycolysis of OSCC cells may provide important therapeutic inspirations. Immunohistochemistry was used to examine protein localization patterns in human OSCC tissues and Western blot was conducted to gauge protein level. Lentivirus transduction was used to overexpress or silence genes of interest. Cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…Also, the consistent increase in lactate concentration after stimulation of the cells known to induce an increase in glycolysis implies that lactate serves as a valid marker of long-term glycolytic activation of immune cells. In line with our work, several recent studies have confirmed a robust association between the rate of glycolysis and lactate levels [45][46][47] . Interestingly, the observed variation in lactate implies large variations in glycolytic metabolism of immune cells in humans.…”
Section: Discussionsupporting
confidence: 92%
“…Also, the consistent increase in lactate concentration after stimulation of the cells known to induce an increase in glycolysis implies that lactate serves as a valid marker of long-term glycolytic activation of immune cells. In line with our work, several recent studies have confirmed a robust association between the rate of glycolysis and lactate levels [45][46][47] . Interestingly, the observed variation in lactate implies large variations in glycolytic metabolism of immune cells in humans.…”
Section: Discussionsupporting
confidence: 92%
“…21 Besides, NEDD4L has been revealed to attenuate the proliferation and glycolysis of oral squamous cell carcinoma cells to exert the tumor-suppressive functions. 22 Further, low-NEDD4L expression has been suggested to be linked to the poor survival of clear cell renal cell carcinoma patients, whereas NEDD4L overexpression weakened the proliferation and migration abilities of clear cell renal cell carcinoma cells. 23 Consistently, this study indicated the tumor suppressor role of NEDD4L in BLCA.…”
Section: Discussionmentioning
confidence: 99%
“…ENO1, also referred to as 2-phospho-D-glycerate hydrolase, is a multifunctional oncoprotein that is present both at the cell surface and in the cytoplasm, contributing to it displaying seven out of ten “hallmarks of cancer” [ 37 , 38 ]. Many studies have demonstrated that the localization and overexpression of ENO1 on the cancer cell surface make it a potential prognostic and diagnostic cancer biomarker as well as an accessible oncotarget [ 39 , 40 ]. Using TCGA HNSCC database, we also found upregulated ENO1 in HNSCC tissues relative to normal counterparts (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%